Förderung des Interesses polnischer DaF-Lehrkräfte an den DACHL-Ländern durch interkollegialen Austausch: Ergebnisse einer Umfrage - Dziurewicz, Elżbieta (Glottodidactica, 2025)
This paper introduces the DACHL-Eulen project as a viable model for enhancing inter est in the DACHL countries – Germany, Austria, Switzerland, Liechtenstein, and Luxembourg – within the context of teaching German as a foreign language in Poland. A key feature of the project is the establishment of a collegial network of German language teachers and researchers that facilitates peer-to-peer support and professional exchange. In addition, this study reports on a survey conducted among 142 Polish teachers of German, including 16 actively involved in the DACHL-Eulen project, to assess their familiarity with the DACHL countries, their preparedness to integrate DACHL-related content into instruction, their level of interest in these countries, and their willingness to engage in further professional development. The findings indicate notable differences between the two groups surveyed. Specifically, the 16 teachers participating in the DACHL-Eulen project exhibited a significantly higher awareness of the cultural and linguistic diversity within the German-speaking world, suggesting that sustained peer exchange exerts a positive influence on teachers’ perceptions and instructional approaches.